2021
DOI: 10.1016/j.marpolbul.2020.111880
|View full text |Cite
|
Sign up to set email alerts
|

In the business of dirty oceans: Overview of startups and entrepreneurs managing marine plastic

Abstract: Plastic pollution, especially in marine environments, is a global problem that is currently inadequately managed. Solutions for marine plastic can occur through policy, behavior change and infrastructure improvements, but also through entrepreneurial ventures and technological innovations. Currently, information about these ventures and innovations is scattered and lacks coherence. This study presents the first comprehensive overview of entrepreneurial and SME led solutions for marine plastic by analyzing a da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 65 publications
0
48
0
Order By: Relevance
“…The integration of the IRS in public and private waste management agencies was found to be synergistically beneficial in terms of environmental and economic improvement and also provides decent and respectable livelihood [238]. With better plastic management, the water bodies will be cleaner, which will help in the tourism sector [239] as well as entrepreneurship [240].…”
Section: Sdg 6 (Ensure Availability and Sustainable Management Of Water And Sanitation For All)mentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of the IRS in public and private waste management agencies was found to be synergistically beneficial in terms of environmental and economic improvement and also provides decent and respectable livelihood [238]. With better plastic management, the water bodies will be cleaner, which will help in the tourism sector [239] as well as entrepreneurship [240].…”
Section: Sdg 6 (Ensure Availability and Sustainable Management Of Water And Sanitation For All)mentioning
confidence: 99%
“…is also becoming popular. Innovative enterprises and start-ups with informal waste pickers in waste clean-up businesses were reported to be symbiotically beneficial [240]. Research and innovation in plastic waste reuse, as well as physical and chemical recycling, will be a great boon as plastic is ubiquitous, and its replacement with alternatives would be difficult and would take a long time.…”
Section: Sdg 6 (Ensure Availability and Sustainable Management Of Water And Sanitation For All)mentioning
confidence: 99%
“…There is also potential to reduce the amount of marine litter through a combination of market-based instruments (environmental taxes, direct payments, deposit-refund schemes etc.) (Oosterhuis et al, 2014), infrastructure for waste disposal improvements, and entrepreneurial ventures and technological innovations (Dijkstra et al, 2020(Dijkstra et al, , 2021.…”
Section: Governance Of Marine Litter Pollutionmentioning
confidence: 99%
“…Technology owners typically have put strategic effort onto the implementation, either by establishing a link towards the local community and/or developing a specific outreach strategy to raise awareness. In line with Dijkstra, van Beukering and Brouwer [33], it was found that many businesses including cleanup and collection offer innovative approaches to raise funding to support waste management. They rely on people power from the local communities to participate in waste management activities.…”
Section: Discussion: Solutions For Developing Countriesmentioning
confidence: 85%
“…However, there is only a limited number of systematic reviews on technological solutions to prevent or reduce marine litter in both the scientific and the 'grey' literature. Dijkstra et al [33], for example, focus on start-ups and recent developments of solutions tackling marine plastic pollution. Schmaltz et al [34] made a comprehensive inventory of technologies currently used or in development to prevent the leakage of plastic pollution or collect existing plastic pollution.…”
Section: Introductionmentioning
confidence: 99%